Correlation between jet lag syndrome and air travel fatigue - Amri, Khaerul; Avia, Imelda; Fahruji, Azis (Intelektual Pustaka Media Utama, 2025)
Long-distance air travel causes travelers to experience travel fatigue. Jet lag syndrome is one of the factors that exacerbate fatigue from air travel. Fatigue can seriously impact travelers with a history of illness. Health emergencies resulting from travel fatigue can even lead to death. A cross-sectional study was conducted to identify the relationship between jet lag syndrome and air travel fatigue. The 117 people who had traveled in the past year had jet lag syndrome and did not meet the exclusion criteria were selected. The questionnaires used the circadian type inventory and the fatigue scale, and validity and reliability were tested. Multiple logistic regression was performed to determine the variables influencing air travel fatigue. The relationship between jet lag syndrome and air travel fatigue was analyzed using Chi-square analysis. Results of the study identified that 53.8% of respondents experienced severe fatigue, and 54.7% experienced severe jet lag syndrome. Jet lag syndrome correlated with air travel fatigue significantly (p = 0.001). Respondents with severe jet lag syndrome experienced severe fatigue. The findings from this study emphasize that addressing jet lag syndrome is necessary to reduce air travel fatigue for overall health.